2014
DOI: 10.1177/0284185113504916
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of cysts, hemangiomas, and metastases of the liver

Abstract: Fa values may play a supportive role in the imaging of liver lesions. Whereas metastases tend to have low ADCs and high Fa values, cysts have high ADCs and low Fa values and hemangiomas have high ADCs and high Fa values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…It was reported that the positive correlation of the FA value with tumour cellularity, that is higher FA, was associated with higher tumour cellularity. 18,[22][23][24] In agreement with previous studies in other organs, our results showed that malignant parotid tumours had higher FA values than benign tumours. In our study, there was a significant difference in the FA values not only between benign and malignant tumours but also between pleomorphic adenomas and adenolymphomas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was reported that the positive correlation of the FA value with tumour cellularity, that is higher FA, was associated with higher tumour cellularity. 18,[22][23][24] In agreement with previous studies in other organs, our results showed that malignant parotid tumours had higher FA values than benign tumours. In our study, there was a significant difference in the FA values not only between benign and malignant tumours but also between pleomorphic adenomas and adenolymphomas.…”
Section: Discussionsupporting
confidence: 92%
“…16,17 The FA or ADC value has a strong correlation with cell density, 18 and malignant tumours usually have a reduced ADC value and an elevated FA value. 19,20 While DTI is widely applied in multiple organs, 18,[21][22][23][24] its application, particularly the FA value in parotid tumours, is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion MRI, particularly DWI, is increasingly used in routine abdominal MRI protocols [5], while the apparent diffusion coefficient (ADC) calculated from DWI has been used to reveal quantitative molecular diffusion. However, DWI merely provides an average ADC over three orthogonal directions, disregarding the anisotropy of tissue structure [10, 11]. It is well known that pancreas is an anisotropic endocrine organ with plenty of vascular supply, as well as complicated anatomy and physiological features [1214].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion weighted (DWI) MRI is an imaging tool which has its origin in the field of neuroradiology, but has been introduced to abdominal imaging in the last decade (9)(10)(11). DWI allows for characterization of biological tissue on the basis of diffusion of water molecules, which is quantified by the apparent diffusion coefficient (ADC).…”
Section: Introductionmentioning
confidence: 99%